2008
DOI: 10.1016/j.jmb.2007.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability of PrP Amyloid Fibrils Controls Their Smallest Possible Fragment Size

Abstract: SUMMARYFibril fragmentation is considered to be an essential step in prion replication. Recent studies have revealed a strong correlation between the incubation period to prion disease and conformational stability of synthetic prions. To gain insight into the molecular mechanism that accounts for this correlation, we proposed that the conformational stability of prion fibrils controls their intrinsic fragility or the size of smallest possible fibrillar fragments. Using amyloid fibrils produced from fulllength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 46 publications
6
63
0
Order By: Relevance
“…However, its strong effect of agitation has recently been found to accelerate the fibril nucleation of several proteins and peptides (14)(15)(16)(17)(18). Interestingly, amyloid fibrils produced by ultrasonicationinduced fibrillation were very short with apparently similar lengths as determined by AFM (15,19), suggesting that short fibrils of homogeneous molecular size are formed efficiently under ultrasonication in combination with the opposing effects of fragmentation and of nucleation (Fig. 1).…”
mentioning
confidence: 93%
“…However, its strong effect of agitation has recently been found to accelerate the fibril nucleation of several proteins and peptides (14)(15)(16)(17)(18). Interestingly, amyloid fibrils produced by ultrasonicationinduced fibrillation were very short with apparently similar lengths as determined by AFM (15,19), suggesting that short fibrils of homogeneous molecular size are formed efficiently under ultrasonication in combination with the opposing effects of fragmentation and of nucleation (Fig. 1).…”
mentioning
confidence: 93%
“…UP in: neurons (in MNDs, NPD, AD, PD, CJD) [27][28][29][30][31][32] UP in: reactive glial cells, microglia, oligodendrocytes [11,13,16,17,33,34] þ þ [1] no [1] no [21] PD: þ þ [35] ALD: þ þ [36] cytoskeleton stabilization; maintaining the proper refractive index in the lens [37,38] (Continued. )…”
Section: Introductionmentioning
confidence: 99%
“…The use of a low chaotropic concentration (∼2 M urea or guanidium chloride) is one of the strategies which can lead to the formation of amyloid fibrils [4,76,122]. Recently the Baskakov's group showed that fragmentation of amyloid fibrils under different physicochemical constraints such as temperature or shaking rate leads to the formation of fibrillar fragments whose size is correlated to the conformationional stability of prion fibrils [68,120].…”
Section: Linkage Between Prp Conformational Dynamics and Prion Pathologymentioning
confidence: 99%